PENGGUNAAN MATHEMATICAL LEARNING-OBJECT BERBASIS BLENDED PICTORIAL ABSTRACK TERHADAP KEMAMPUAN REFLECTIVE ABSTRACTION MAHASISWA: - - mulyanti, Yanti Mulyanti; Darhim; Turmudi (Jurnal Padegogik, 2025)
This research aims to determine the use of Mathematical Learning Objects based on blended pictorial abstracts on the Reflective Abstraction abilities of students in the mathematics selection category. The subjects in this study were 107 students of the Mathematics Education Study Program who contracted secondary school mathematics courses (or equivalent) from four private universities on the island of Java. The subjects were taken purposively, the selection of universities was carried out randomly. The results obtained are: (1) There are differences in the Reflective Abstraction abilities of students who learn using Mathematical Learning Objects based on blended Pictorial abstract based on the prerequisite knowledge ability (KPP) categories of low, medium, high, with sig.0.006; (2) Based on further tests, to see which one is better, the results obtained are sig. 0.008 for KRA_KPPR and KR A-KPPS; sig. 0.002 for KRA_KPPR and KRA-KPPST; and sig. 0.500 for KRA_KPPS and KRA- KPPT. This means that: the Reflective abstraction ability of students in the medium KPP category is better than the students in the low KPP category, the Reflective abstraction ability of students in the high KPP category is better than the students in the low KPP category, the Reflective abstraction ability of students in the high KPP category is no better than the students in the medium KPP category.